Auditor Reporting under Section 404: The Association between the Internal Control and Going Concern Audit Opinions - Goh, Beng Wee; Krishnan, Jayanthi; Li, Dan (Contemporary Accounting Research, 2013)
Section 404 of the Sarbanes-Oxley Act and Auditing Standard No. 2 introduced integrated audits of internal control over financial reporting and the financial statements. Since the internal control and audit reports are joint products of the audit process, we examine whether the issuance of an internal control material weakness opinion (MWO) influences, other things equal, the issuance of a going concern audit opinion (GCO). Using a sample of financially stressed companies, we find that the issuance of a MWO increases the likelihood of a GCO, suggesting that auditors do respond to the uncertainty surrounding a MWO by issuing a GCO. Further analyses reveal that the positive association between MWO and GCO obtains for company-level material weaknesses, which are known to be difficult to “audit-around”, and for more litigious industries. We also compare these results with those for a Section 302 sample with manager-reported (but not audited) material weaknesses, and find that the material weakness reported under Section 302 does not impact the GCO. Hence, the auditors respond to the uncertainty surrounding material weaknesses only when they issue MWOs, and not due to the existence of material weaknesses per se – that is, the issuance of a MWO seems to induce further conservatism in the auditor’s GCO decision. We conclude that researchers and policymakers should consider the overall effect of Section 404 on the financial statement audit.